A Cognitive Model of Chinese Word Segmentation for Machine Translation - Wu, Zhijie (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2011)
The Chinese language, unlike English, is written without marked word boundaries, and Chinese word segmentation is often referred to as the bottleneck for Chinese-English machine translation. The current word-segmentation systems in machine translation are either linguistically-oriented or statistically-oriented. Chinese, however, is a pragmatically-oriented language, which explains why the existing Chinese word segmentation systems in machine translation are not successful in dealing with the language. Based on a language investigation consisting of two surveys and eight interviews, and its findings concerning how Chinese people segment a Chinese sentence into words in their reading, we have developed a new word-segmentation model, aiming to address the word-segmentation problem in machine translation from a cognitive perspective.